The Relationship Between Nurses' Loyalty And The Level Of Inpatient Satisfaction At The Sula Islands Regency Hospital - Eka Daya Liamanu; Risna Yekti Mumpuni; Registra Trigantara (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Healthcare workers are a key component in providing healthcare services to the community, contributing to the achievement of health development goals. Hospitals rely heavily on the quality of care provided by the hospital. However, some services still fall short of patient expectations, and patient satisfaction levels remain substandard, impacting hospital development. Nurses also need to demonstrate loyalty in providing patient care. Suboptimal levels of loyalty negatively impact the quality of hospital services, thus impacting patient satisfaction. This study aims to determine whether there is a relationship between nurse loyalty and the level of satisfaction of inpatients at the Sula Islands Regency Hospital. Methods: The research design used a quantitative correlational design with a cross-sectional approach. The variables in this study were the independent variable, namely nurse loyalty, while the dependent variable was the level of satisfaction of inpatients at the Sula Islands Regency Hospital. The population of this study was all nurses, namely 45 nurses and 439 patients calculated on average per year, at the Sula Islands Regency Hospital. And the sample in this study was 45 nurses using total sampling and 81 inpatients with a sampling technique using purposive sampling. The instruments used in this study were a nurse loyalty questionnaire and a patient satisfaction questionnaire. The data analysis method used was the Spearman rank test. Results: The results of the study proved that the loyalty of nurses who were loyal to the level of patient satisfaction was satisfied, namely 10 (32.3%), and 4 (12.9%) with a very satisfied level of patient satisfaction. Conclusions: The results of the Spearman rank test show that there is a relationship between nurse loyalty and the level of patient satisfaction at the Kepulauan Regency Regional Hospital, with a p value = (0.025) < (0.05), meaning that increasing nurse loyalty is very important to improve the quality of nursing services and increase patient satisfaction in the hospital environment.